Make it through tough times as a group: on the importance of collective predictors of protection behavior and policy acceptance of mitigation measures during the COVID-19 pandemic - Annedore Hoppe; Anna Maria Becker; Immo Fritsche; Johannes Lautenbacher (Social Influence)
During crises like a pandemic, citizens must adapt to disruptive policies. We challenge the view that policy support depends mainly on personal costs and benefits (e.g., health threats) and propose that collective factors, such as ingroup norms and collective efficacy, are equally important. Across three measurement points during Germany’s first COVID-19 wave (March–May 2020, N = 469), we found that both personal and collective factors independently predicted protection behavior and policy acceptance. Additional longitudinal analyses revealed, that for individuals strongly identified with their ingroup, early policy acceptance enhanced collective efficacy and norm perceptions, which subsequently increased later acceptance. These findings highlight collective agency as crucial for coping with crises and provide insights for addressing other global challenges, such as climate change.